2012
DOI: 10.1371/journal.pone.0043850
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 14 Organic Solvents and Carriers for Screening Applications in Zebrafish Embryos and Larvae

Abstract: Zebrafish are rapidly growing in popularity as an in vivo model system for chemical genetics, drug discovery, and toxicology, and more recently also for natural product discovery. Experiments involving the pharmacological evaluation of small molecules or natural product extracts in zebrafish bioassays require the effective delivery of these compounds to embryos and larvae. While most samples to be screened are first solubilized in dimethyl sulfoxide (DMSO), which is then diluted in the embryo medium, often thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
112
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(136 citation statements)
references
References 40 publications
12
112
0
1
Order By: Relevance
“…The observed slight excess toxicity in embryos may indicate a specific interaction but it is unlikely that this is related to the neurotoxic mode of action of APM (Arufe et al, 2007) given that the differentiation of spinal and motoneurons first starts at around 18-21 hpf (Bernhardt et al, 1990). The lack of toxicity or weaker toxicity in later embryonic life stages has also been identified for some other compounds and by other scientists (Henn and Braunbeck, 2011;Maes et al, 2012) .The analyses of 2h short term exposure windows supported a potential stage-specific sensitivity. The critical window of exposure could be assigned to the period of 0 -4 hpf.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The observed slight excess toxicity in embryos may indicate a specific interaction but it is unlikely that this is related to the neurotoxic mode of action of APM (Arufe et al, 2007) given that the differentiation of spinal and motoneurons first starts at around 18-21 hpf (Bernhardt et al, 1990). The lack of toxicity or weaker toxicity in later embryonic life stages has also been identified for some other compounds and by other scientists (Henn and Braunbeck, 2011;Maes et al, 2012) .The analyses of 2h short term exposure windows supported a potential stage-specific sensitivity. The critical window of exposure could be assigned to the period of 0 -4 hpf.…”
Section: Discussionmentioning
confidence: 61%
“…Occasionally significant differences in observable zebrafish embryo acute toxicity have been reported depending on the duration of exposure and in relation to whether early cleavage stages had been included or not. For instance, initiation of exposure at 24 hpf (hours post fertilisation) instead of 0-2 hpf reduced the sensitivity for acute toxicity of 3,4-dichloroaniline and some solvents (Henn and Braunbeck, 2011;Maes et al, 2012). During a screen of toxicity of compounds from an internal databases (UFZ-Department Bioanalytical ecotoxicology, Leipzig) we also observed that the acetylcholinestrase inhibitor APM may provoke increased toxicity in fish embryos when early embryonic stages are included in the exposure period.…”
Section: Introductionmentioning
confidence: 78%
“…DMSO has shown to be one of the least embryotoxic solvents for ZF. The embryotoxicity and acute toxicity studies of DMSO done in ZF embryos indicate its safety up to 1% v/v for morphological endpoints [4,8,30,47,48]. However, Weigt et al [21] reported a doubling of affected embryos in the control groups with 0.5% DMSO compared to controls without (i.e.…”
Section: Use Of Solventmentioning
confidence: 99%
“…Though generally found to be low-toxic, at high concentrations, glycerine could impair blood circulation (Maes et al, 2012).…”
Section: Glycerinementioning
confidence: 99%